2020
DOI: 10.1128/mbio.02092-20
|View full text |Cite
|
Sign up to set email alerts
|

The ZIP Code of Vesicle Trafficking in Apicomplexa: SEC1/Munc18 and SNARE Proteins

Abstract: Apicomplexans are obligate intracellular parasites harboring three sets of unique secretory organelles termed micronemes, rhoptries, and dense granules that are dedicated to the establishment of infection in the host cell. Apicomplexans rely on the endolysosomal system to generate the secretory organelles and to ingest and digest host cell proteins. These parasites also possess a metabolically relevant secondary endosymbiotic organelle, the apicoplast, which relies on vesicular trafficking for correct incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 89 publications
(158 reference statements)
3
46
0
Order By: Relevance
“…The description of an interaction between the C‐terminal tail of SORTLR with AP1 and Vps proteins suggests a concerted role of these complexes in the trafficking of ROPs and MICs via a clathrin‐dependent process (Sloves et al., 2012). A recent study shows that the trafficking of vesicles to their specialized compartments depends on SNARE proteins (Bisio et al., 2020). Syntaxin (Stx)‐like SNARE protein 12 (Stx12) localizes to the ELC and is involved in the trafficking of proteins to rhoptries and micronemes as well as to the apicoplast.…”
Section: Rhoptry Organelle Biogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The description of an interaction between the C‐terminal tail of SORTLR with AP1 and Vps proteins suggests a concerted role of these complexes in the trafficking of ROPs and MICs via a clathrin‐dependent process (Sloves et al., 2012). A recent study shows that the trafficking of vesicles to their specialized compartments depends on SNARE proteins (Bisio et al., 2020). Syntaxin (Stx)‐like SNARE protein 12 (Stx12) localizes to the ELC and is involved in the trafficking of proteins to rhoptries and micronemes as well as to the apicoplast.…”
Section: Rhoptry Organelle Biogenesismentioning
confidence: 99%
“…Syntaxin (Stx)‐like SNARE protein 12 (Stx12) localizes to the ELC and is involved in the trafficking of proteins to rhoptries and micronemes as well as to the apicoplast. Disruption of Stx12 resulted in a decreased amount of mature microneme and rhoptry proteins along with a severe defect in invasion (Bisio et al., 2020).…”
Section: Rhoptry Organelle Biogenesismentioning
confidence: 99%
“…Although Rab11A has been shown to be critical in constitutive secretion of dense granules, this is not a triggered event [ 102 ]. In addition, no Toxoplasma ’s SNARE proteins have been detected at the site of microneme and rhoptry secretion site in the very apical plasma membrane [ 103 ]. The most forward localizing SNARE in the secretory pathway identified is a syntaxin, TgStx12, which is critical in trafficking of proteins from ELC to the micronemes and rhoptries, but not for their secretion.…”
Section: Resultsmentioning
confidence: 99%
“…The function of the Kelch13 compartment and cytostome-like structures in late schizont and merozoites remains to be elucidated. It could either represent a repurposing of these endocytosis-linked structures (Spielmann et al, 2020) for host cell invasion and the establishment of the parasite in a new host cell or serve an endocytosis-related function in schizonts, as it has been recently shown that schizonts still appear to endocytose host cell hemoglobin (Bisio et al, 2020).…”
Section: Discussionmentioning
confidence: 99%